Strategi Kepala Sekolah dalam Membangun Mutu Pendidikan di MTsN Model Pare, Kediri - A’an Yusuf Khunaifi (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2018)
The demand of quality education the more days pass more gain strength. This phenomenon appear along with the condition of peoples needs growing rapidly. That indispensable priscipal professional, were able to establish that the quality of education quality and considered superior public interest. The focus of this study are three things, that is: a) principal behavior in the build quality of education. b) strategy principals in building the quality of education. to answer the focus of the study, the researchers used a qualitative approach, nid of case studies. Methods of data collection use include: a) deep interview. b) oservation. c) study documentation. Data from the three techniques are organized, interpreted, and analyzed repeatedly. To avoid mistakes, then held data validity checking using the method of: a) triangulation between data sources, comparing data from interviews. b) checking the accuracy of information to the informant. c) discuss and consult data by the competent authorities. The results of this study found: 1) behavior of the principals in building a quality of education that is: a) motivate. b) establish good communation and warm. c) in volve all members of the school, and example to the school community in an effort to build the quality of education. 2) strategy principal in building the quality of education that is: a) build a strong team work and soulid. b) build a family. c) to support and facilitate teachers in the development of quality and competene. d) the division of duties and performance to match the capabilities of each subordinate. e) working closely with other agencies. f) to collaoration with the mass media. g) having a clear quality targets.